Theories of suicide : past, present and future - Gunn, John F. (Charles C Thomas, Publisher, Ltd., 2014)
Some researchers in the field of suicidology think that the old theories of suicide are too constraining and impede advances in the understanding of suicide. However the book's authors are not quite so critical of past theories. In the book they review the classic theories of suicide, both psychological and sociological, because they are the foundation of our current theories and also propose the skeletons of possible future theories. The goal of the text is to present researchers with theories to guide their research, encourage them to modify these theories, perhaps meld them together in some.